In vitro cytotoxicity (irritant potency) of toothpaste ingredients - Shaira R. Kasi; Sanne Roffel; Mutlu Özcan; Susan Gibbs; Albert J. Feilzer (PLoS ONE, 2025)
Purpose This study aimed to determine the cytotoxicity (irritant potency) of toothpaste ingredients, of which some had known to have sensitizing properties. Materials From the wide variety of toothpaste ingredients, Xylitol, Propylene glycol (PEG), Sodium metaphosphate (SMP), Lemon, Peppermint, Fluoride, Cinnamon, and Triclosan and Sodium dodecyl sulphate (SDS) have been selected for evaluation of their cytotoxic properties. Methods Reconstructed human gingiva (RHG) were topically exposed to toothpaste ingredients at different concentrations. The compound concentration resulting in 50% cell death (EC50) and 10% cell death (EC10) was determined by the MTT assay. Detrimental effects in tissue histology were observed by hematoxylin & eosin staining of tissue sections followed by microscopy. Results While Xylitol, PEG, and SMP did not appear to affect cell viability or tissue histology, the concentrations of Lemon, Peppermint, Cinnamon and SDS present in toothpastes exceeded the EC50 value and resulted in clear detrimental effects in tissue histology, indicating that they could harm the oral mucosa. Triclosan and Fluoride concentrations in the tested toothpastes exceeded the EC10 value but remained below the EC50 value with no clear detrimental effects in tissue histology. Clinical significance Manufacturers are encouraged to comply with higher standards of quality and safety for toothpaste.